2012
DOI: 10.1186/1471-2164-13-627
|View full text |Cite
|
Sign up to set email alerts
|

2009 pandemic H1N1 influenza virus elicits similar clinical course but differential host transcriptional response in mouse, macaque, and swine infection models

Abstract: BackgroundThe 2009 pandemic H1N1 influenza virus emerged in swine and quickly became a major global health threat. In mouse, non human primate, and swine infection models, the pH1N1 virus efficiently replicates in the lung and induces pro-inflammatory host responses; however, whether similar or different cellular pathways were impacted by pH1N1 virus across independent infection models remains to be further defined. To address this we have performed a comparative transcriptomic analysis of acute phase response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 48 publications
2
32
0
Order By: Relevance
“…Previous pH1N1 infections of rhesus macaques have relied on high-dose administration of virus to tracheal, nasal, ocular, and oral mucosal surfaces. This resulted in limited clinical signs despite the recovery of virus at multiple days postinfection (6,11). In this study, we challenged naive animals with a mixed-particle aerosol composed of large and small virus particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous pH1N1 infections of rhesus macaques have relied on high-dose administration of virus to tracheal, nasal, ocular, and oral mucosal surfaces. This resulted in limited clinical signs despite the recovery of virus at multiple days postinfection (6,11). In this study, we challenged naive animals with a mixed-particle aerosol composed of large and small virus particles.…”
Section: Resultsmentioning
confidence: 99%
“…These studies revealed species-specific differences in the host responses between rhesus and cynomolgus macaques. Cynomolgus macaques infected with strain influenza A/California/04/2009 (H1N1) (pH1N1 Cal04) virus exhibited moderately severe clinical signs by day 6 postinfection, with a concurrent activation of the inflammatory response genes in the lung (11). In comparison, rhesus macaques infected with the same pH1N1 strain remained asymptomatic despite sustained viral shedding for 21 days postinfection (10).…”
mentioning
confidence: 99%
“…Tissues collected at necropsy on day 4 showed that the pandemic virus replicated to a greater extent in the lower respiratory tract, causing diffuse alveolar damage. A later study found that, although the pandemic virus infects mice, pigs and macaques, it elicits different sets of transcriptional responses in the three species (Go et al, 2012). …”
Section: Experimental Infections Of Nhps With Human Influenza VImentioning
confidence: 99%
“…Clinical symptoms associated with the 2009 pandemic H1N1 strain (H1N1 pdm09) include mild respiratory irritations that extend up to severe pneumonia, associated with acute respiratory distress syndrome (ARDS) with the gradual progress of infection (Chowell et al, 2009;Perez-Padilla et al, 2009;Go et al, 2012). The H1N1 pandemic that initiated in 2009 resulted in nearly 300,000 deaths globally within the first year of its outbreak (Dawood et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The H1N1 pandemic that initiated in 2009 resulted in nearly 300,000 deaths globally within the first year of its outbreak (Dawood et al, 2012). A distinctive feature of influenza virus infection is a successful viral entry into the host system followed by subsequent destruction of the host immune responses and inception of disease (Go et al, 2012;de Jong et al, 2006;Kobasa et al, 2007). Continuous antigenic variations occur in influenza A virus that ensure its competent replication inside the human host (Schmolke and Garcia-Sastre, 2010).…”
Section: Introductionmentioning
confidence: 99%